Homomorphisms of Complex Kumjian-Pask Algebras - Rosjanuardi, Rizky; Mulyaning Asih, Endang Cahya; Masta, Al Azhary (Journal of the Indonesian Mathematical Society, 2023)
Let Λ and Γ be row finite k-graphs without sources. We show that ∗-algebra homomorphisms ϕ : KPC(Λ) → KPC(Γ) extend to ∗-algebra homomorphisms ϕ¯ : C∗(Λ) → C∗(Γ). We also examine necessary and sufficient conditions for algebra homomorphisms between complex Kumjian-Pask algebras KPC(Λ) and KPC(Γ) which are ∗-preserving.